The feeling of the past in Le Nez sur la vitre by Abdelkader Djemai - Bekhedidja, Nabila (Romanica Olomucensia, 2019)
Le Nez sur la vitre (The Nose on the Glass), published in 2004, tells the story of an immigrant man in France who goes to meet his son who does not respond to his letters. At the end of the road, he will find, behind the glass of the coach, his past and his memories. Images of his childhood in his native douar during the war of national liberation pass rapidly before his eyes. On arriving at the prison where his son is serving a sentence, the father learns that his son ended his own life in his cell the day before. Abdelkader Djemai paints a character who compensates for his poor command of the French language by keeping his eyes glued to the glass, a man in a society where he still remains a stranger. The novel also addresses the hardship of these dignified and hardworking emigrants. The sociohistorical approach allows us to consider the relationship between text and history, as well as the social universe in the novel. The aim of this study is to shed light on the present and the painful past of a social group and to resurrect (feel) the feeling of regret and memory of the past of this character. Le Nez sur la vitre is a novel about the breakdown of family ties, the conflict between generations, memory, and the history of Algeria. Abdelkader Djemai thus tells the story of this working father, whose name is unknown until the end of the novel and who represents the chibanis of France. The author presents this character to express his regrets and tell of his pain.
Keywords: memories; history; immigrant; past; present